Existência global de soluções para certos sistemas parabólicos não lineares - Webler, Claudete Matilde (2005)
In this work, we study the global existence of smooth solutions for certain systems of the form ut + f(u)x = Duxx, where u and f are vectors and D is a positive, constant and diagonalizable matrix. We assume that the initial condition u0 satisfies jju0¡ujjL1(IR) < r, where u is a fixed vector, f is defined in the ball of the center u of radius r and jju0¡ujjL2(IR) is su±ciently small. We show how our results apply to the equations of gas dynamics and we include a result which shows that for the Navier-Stokes equations of compressible flow, smoothing of initial discontinuities must occur for velocity and energy, but not for the density.